The Synaptic Extracellular Matrix: Long-Lived, Stable, and Still Remarkably Dynamic - Dankovich, Tal M.; Rizzoli, Silvio O. (Frontiers in Synaptic Neuroscience, 2022)
In the adult brain, synapses are tightly enwrapped by lattices of extracellular matrix that consist of extremely long-lived molecules. These lattices are deemed to stabilize synapses, restrict the reorganization of their transmission machinery, and prevent them from undergoing structural or morphological changes. At the same time, they are expected to retain some degree of flexibility to permit occasional events of synaptic plasticity. The recent understanding that structural changes to synapses are significantly more frequent than previously assumed (occurring even on a timescale of minutes) has called for a mechanism that allows continual and energy-efficient remodeling of the ECM at synapses. Here, we review recent evidence for such a process based on the constitutive recycling of synaptic ECM molecules. We discuss the key characteristics of this mechanism, focusing on its roles in mediating synaptic transmission and plasticity, and speculate on additional potential functions in neuronal signaling.